2014
DOI: 10.1007/s00429-014-0877-7
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous-cue prospective memory involving incremental updating of working memory: an fMRI study

Abstract: Activation of the bilateral dorsal anterior insula, a component of the central salience network, was found to be unique to this 'endogenous-cue prospective memory task' in comparison to previously reported exogenous- and endogenous-cue prospective memory tasks without incremental working memory updating. Thus, the findings of the present study highlight the important role played by the dorsal anterior insula in incremental working memory updating that is integral to our endogenous-cue prospective memory task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…The first main finding is that the ERs were significantly greater during the performance of the PM task following inhibitory cTBS over the right rostral prefrontal cortex, compared with cTBS over a control region. This finding is consistent with those of previous TMS studies and a body of functional neuroimaging investigations that demonstrated the involvement of the rostral prefrontal cortex (BA 10) in the mediation of PM processes (Burgess et al, 2008 , 2011 ; Costa et al, 2011 , 2013 ; Halahalli et al, 2014 ). Moreover, consistent with previous evidence, the rostral prefrontal cortex has been implicated in WM and other PM tasks (Ramnani and Owen, 2004 ; Gilbert et al, 2006 ; Burgess and Wu, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The first main finding is that the ERs were significantly greater during the performance of the PM task following inhibitory cTBS over the right rostral prefrontal cortex, compared with cTBS over a control region. This finding is consistent with those of previous TMS studies and a body of functional neuroimaging investigations that demonstrated the involvement of the rostral prefrontal cortex (BA 10) in the mediation of PM processes (Burgess et al, 2008 , 2011 ; Costa et al, 2011 , 2013 ; Halahalli et al, 2014 ). Moreover, consistent with previous evidence, the rostral prefrontal cortex has been implicated in WM and other PM tasks (Ramnani and Owen, 2004 ; Gilbert et al, 2006 ; Burgess and Wu, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…This has been further supported by a meta-analyses study, which showed that a variety of n-back tasks provoked activation in the bilateral rPFC (Owen et al, 2005 ). More recently, a functional magnetic resonance imaging (fMRI) study using endogenous PM paradigm involving incremental updating of WM has reported activation of the left rPFC during the performance of WM (Halahalli et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Halahalli et al . reported that the cerebellum was involved in the endogenous-cue prospective memory processing41. To our knowledge, the association between altered connectivity between the hippocampus and the cerebellum and the prospective memory has not been reported before.…”
Section: Discussionmentioning
confidence: 75%
“…Increased cognitive effort is also associated with enhanced engagement in BA 10 (see Fig. 9), as in the case of a secondary task overlapping the main one (Minamoto et al, 2015;Momennejad and Haynes, 2013), as well as a prospective memory task that requires incremental updating of working memory (Halahalli et al, 2015). Hence, in our study, we hypothesized enhanced cognitive load in controls (lacking in specific motor knowledge) due to increased kinematics processing in anticipation of the motor imagery task.…”
Section: Discussionmentioning
confidence: 84%